Natural Food Coating from Lac : Present Conditions and Development Prospect in East Nusa Tenggara Province - Samuel Pakan (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2007)
Lac is secreted by Laccifer lacca kern that has been widely used as food coating materials. To get the best food coatings from lac, the sticklac which processed need to be converted to seedlac and further become shellac. It is one of the potential commodities in East Nusa Tenggara Timur Province. However, more work has to be done for improving its productivity as well as its quality. Key words : lac, Laccifer lacca kern, food coating.